Enhancing patients' hospital satisfaction by taking advantage of interpersonal similarity. (May 2016) - Luther, Louisa; Benkenstein, Martin; Rummelhagen, Katja
Abstract: According to the customer-to-customer literature, other customers are a prominent influence factor of service perception. Until now, the influence of other patients in shared rooms has been widely ignored in the hospital satisfaction literature. To guide the potential influence of other patients in a positive direction, we examined the effectiveness of interpersonal similarity. Using a scenario-based experimental design, we find that a similar perceived roommate leads to more positive feelings toward hospitalization and higher affective and behavioral attraction to this roommate. The findings indicate that higher attraction ratings mediate participants' increased satisfaction judgements of hospitals. Therefore, assigning roommates by their similarity is an appropriate procedure to raise patients' satisfaction ratings. To gain convenient implications for which similarity dimensions are especially important in every day hospital work life, we conducted group interviews with nurses. Age, habitualities and disease are promising attributes to implement the experimental results in hospitals. Highlights: Influence of interpersonal similarity on attraction ratings for hospital roommates. Influence of attraction ratings on overall satisfaction with the hospital. Behavioral and affective attraction ratings act as a mediator. Similarity dimensions for everyday work life in hospitals. Age, habituality, and disease as similarity dimensions for satisfying allocation.